Exercise intensity and energy expenditure of a multicomponent home-based training program: Xiangya hospital circuit training (X-CircuiT) - Hu, Peng; Zhang, Wenliang; Ripley-Gonzalez, Jeffrey W.; Xie, Kangling; Gong, Xun; Cao, Zeng; Shen, Yanan; You, Baiyang; Dun, Yaoshan; Liu, Suixin (Frontiers in Public Health, 2022)
Introduction Our previous studies showed that Xiangya Hospital Circuit Training (X-CircuiT) effectively improved physical fitness and reversed pre-frailty in community-dwelling older adults. This study aimed to explore the generalizability and applicability of X-CircuiT in different aged populations in the context of exercise intensity and energy expenditure. Methods We prospectively recruited 72 community-dwelling sedentary adults, twelve adults divided into 6 age groups ranging from 20 to 80 years old and separated by decades. Cardiopulmonary exercise testing was performed to determine peak heart rate (HRpeak). An individual HR-oxygen consumption regression equation was fit for each participant, and then a session of remote heart rate monitored X-CircuiT was performed. Exercise intensity (%HRpeak) and energy expenditure of X-CircuiT among the six age groups were assessed. Further sub-analysis was conducted by dividing the participants by peak metabolic equivalent (MET) values, <5 METs, 5–7 METs, and more than 7METs to explore the relationship between maximum exercise capacity and exercise intensity of X-CircuiT. Results The average %HRpeak of X-CircuiT for subjects in the 20–29, 30–39, 40–49, 50–59, 60–69, and 70–80 age groups were 54 ± 6, 59 ± 8, 60 ± 8, 62 ± 5, 66 ± 10, and 67 ± 13, respectively (p = 0.008); and the average energy expenditure was 121.9 ± 26.5, 123.3 ± 33.8, 129.2 ± 40.9, 130.9 ± 31.8, 146.8 ± 29.0, and 125.0 ± 28.4 kcal, respectively. The average %HRpeak for the warm-up, aerobic, acupoint patting, resistance, and stretching stages in overall subjects was 61 ± 9, 70 ± 10, 70 ± 10, 63 ± 9, and 57 ± 9, respectively. Furthermore, when subjects were divided by peak METs, it was found that the lower the peak METs, the greater the value of the relative exercise intensity indicators. The aerobic and acupoint stages of X-CircuiT could illicit a response of high intensity for those with peak METs <5, moderate intensity in those with peak METs of 5–7, and low-intensity for those with peak METs of more than 7. Conclusion Xiangya Hospital Circuit Training followed the principle of low-intensity warm-up and medium-intensity training with multicomponent exercise training. It is classified as a moderate-intensity exercise for sedentary middle-aged and older adults, or those with a maximum exercise capacity of 5–7 METs, and is classified as a low-intensity exercise for young people.